Penerapan Terapi Non Farmokologi Senam Hipertensi untuk Menurunkan Tekanan Darah Tinggi pada Pasien Hipertensi di Ruangan Flamboyan - Sugiarto, Riki; Susanti, Fajar; Samsuni, Samsuni (Jurnal Ilmu Medis Indonesia, 2024)
Purpose: aims to determine the success rate of hypertension exercise in cases of weakness Methodology/approach: This study used a case study of the management of patients with hypertension at PSTW Budi Mulia 1 Cipayung, implemented for 12 days, which resulted in a reduction in hypertension levels in patients. Results: Based on the evaluation results, there was a significant reduction in blood pressure seen from changes in blood pressure before and after hypertension exercise therapy was carried out in the elderly for 5 minutes. Blood pressure results were obtained at 160/90 mmHg, 158/80 mmHg, BP= 155/95 mmHg, 158/98 mmHg, 155/90 mmHg, 150/90 mmHg, 140/90 mmHg, 148/80 mmHg, BP= 139/95 mmHg, 138/98 mmHg, 125/90 mmHg, 150/90 mmHg. It can be concluded that after implementing hypertension exercises in the elderly with implementation 12 times for 5 min, significant evaluation results were obtained where there was a decrease in blood pressure levels in hypertensive patients. Limitations: This case study is still being considered so that other researchers can conduct research according to practical standards and carried out within a 12 day period. Contribution: I would like to thank the parties who contributed to this work on this case study and have been involved in completing this case study.